Integrated single-cell RNA sequencing reveals the tumor heterogeneity and microenvironment landscape during liver metastasis in adenocarcinoma of esophagogastric junction - Xu, Junrui; Sadiq, Ussama; Zhao, Wangruizhi; Xia, Hengbo; Liu, Yiwei; Zhang, Renquan; Xu, Aman (Frontiers in Immunology, 2025)
BackgroundAdenocarcinoma of the esophagogastric junction (AEGJ) is a highly aggressive tumor that frequently metastasizes to the liver. Understanding the cellular and molecular mechanisms that drive this process is essential for developing effective therapies.MethodsWe employed single-cell RNA sequencing to analyze the tumor heterogeneity and microenvironmental landscape in patients with AEGJ liver metastases. This approach enabled us to characterize the diverse cell populations involved in the liver metastatic process.ResultsOur analysis revealed a significant involvement of fibroblasts and mural cells in AEGJ liver metastasis. We identified a specific fibroblast type in AEGJ liver metastasis and observed distinct gene expression patterns between adenocarcinoma of the esophagogastric junction and other stomach adenocarcinomas. Our study demonstrated high expression of the SFRP2 gene in pericyte cells during the liver metastasis of AEGJ. The incorporation of GEO, TCGA, and immunofluorescence staining of SFRP2 expression enhanced our study. High expression of SFRP2 in pericytes may influence vascular stability and angiogenesis through the Wnt pathway.ConclusionOur study provides novel insights into the cellular interactions and molecular mechanisms that underlie AEGJ liver metastasis. Targeting the identified subtype of fibroblasts or influencing SFRP2 gene expression in pericytes may offer new therapeutic strategies for combating this aggressive tumor.